2018
DOI: 10.2478/ethemes-2018-0022
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for and Against the Validity of Efficient Market Hypothesis

Abstract: The concept of an efficient financial market, in literature known as efficient market hypothesis (EMH), has had a long and difficult development path from the idea itself to its final conception, as one of the central paradigms in modern finance. It has been tested and critically reviewed for decades, and the two basic types of problems it has encountered are theoretical paradoxes and market anomalies. The aim of the paper is to examine the validity of EMH through various financial market efficiency tests and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
0
7
0
1
Order By: Relevance
“…This means that share prices contain company reports and public information about the firm. Strongform efficiency markets have stock prices that rapidly adjust to any information, including inside information (Lekovic, 2018). Therefore, no investor can earn excess returns using any information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This means that share prices contain company reports and public information about the firm. Strongform efficiency markets have stock prices that rapidly adjust to any information, including inside information (Lekovic, 2018). Therefore, no investor can earn excess returns using any information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, investors cannot use public information to obtain above-normal profit levels. Third, market efficiency is a strong form, a situation where prices not only reflect all published information but also the information contained in the fundamental analysis of companies and the economy (Leković, 2018).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Investment Management and Financial Innovations, Volume 20, Issue 1, 2023 http://dx.doi.org/10.21511/imfi.20 (1).2023. 19 All events can affect economic conditions (Febriandika & Rahayu, 2021). Likewise, the volatility of rising oil prices certainly made the market more out of control.…”
Section: Introductionmentioning
confidence: 99%
“…EMH has been a controversial theory and has generated serious debate in the investment finance literature. Over the years of research, epistles in the financial literature have not come to a consensus on the absence or presence of the validity of EMH hypothesis [12]. In testing EMH in the weak form, several studies result have shown random walk in stock markets outside the Nigerian stock exchange; including the work of [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%